Effects of carbon levels on shoot growth and root characteristics of different kenaf (Hibiscus cannabinus L.) varieties grown on sandy bris soil - Hossain, Md. Delwar; Musa, Mohamed Hanafi; Jol, Hamdan; Abdul Hamid, Hazandy (Academic Journals, 2012)
The effects of carbon levels on shoot growth and root characteristics of five kenaf varieties were assessed in a shade house experiment. The kenaf plants were grown in pots containing sandy beach ridges interspersed with swales (BRIS) soil. Organic carbons at levels of 0, 10, 20 and 30 t ha-1 were applied to pots using organic fertilizer. The plants at carbon levels 20 t ha-1 had the highest plant height, leaf area, shoot and root dry matter, total root length, root surface area, total root volume, and number of root tips. Increasing carbon levels had negatively affected shoot growth and root morphology of all varieties under study. There was an obvious difference in response to carbon levels among the five varieties with HC2 showing the highest performance in terms of shoot growth and root characteristics. These results provide significant insights into limitations and opportunities for growing of kenaf in BRIS soil with better organic carbon management.